Strain-time curve analysis by speckle tracking echocardiography in cardiac resynchronization therapy: Insight into the pathophysiology of responders vs. non-responders. Issue 1 (December 2015) - To, Andrew; Benatti, Rodolfo; Sato, Kimi; Grimm, Richard; Thomas, James; Wilkoff, Bruce; Agler, Deborah; Popović, Zoran
Abstract Background Patients with non-ischemic heart failure etiology and left bundle branch block (LBBB) show better response to cardiac resynchronization therapy (CRT). While these patients have the most pronounced left ventricular (LV) dyssynchrony, LV dyssynchrony assessment often fails to predict outcome. We hypothesized that patients with favorable outcome from CRT can be identified by a characteristic strain distribution pattern. Methods From 313 patients who underwent CRT between 2003 and 2006, we identified 10 patients who were CRT non-responders (no LV end-systolic volume [LVESV] reduction) with non-ischemic cardiomyopathy and LBBB and compared with randomly selected CRT responders (n  = 10; LVESV reduction ≥15 %). Longitudinal strain (εlong ) data were obtained by speckle tracking echocardiography before and after (9 ± 5 months) CRT implantation and standardized segmental εlong -time curves were obtained by averaging individual patients. Results In responders, ejection fraction (EF) increased from 25 ± 9 to 40 ± 11 % (p  = 0.002), while in non-responders, EF was unchanged (20 ± 8 to 21 ± 5 %, p  = 0.57). Global εlong was significantly lower in non-responders at pre CRT (p  = 0.02) and only improved in responders (p  = 0.04) after CRT. Pre CRT septal εlong -time curves in both groups showed early septal contraction with mid-systolic decrease, while lateral εlong showed early stretch followed by vigorous mid to late contraction. Restoration of contraction synchrony was observed in both groups, though non-responder remained low amplitude of εlong . Conclusions CRT non-responders with LBBB and non-ischemic etiology showed a similar improvement of εlong pattern with responders after CRT implantation, while amplitude of εlong remained unchanged. Lower εlong in the non-responders may account for their poor response to CRT.